2008
DOI: 10.1021/ol8024617
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Addition of Organozinc Reagents to 2-Sulfonyl Cyclic Ethers: Stereoselective Synthesis of Manassantins A and B

Abstract: A convergent route to the synthesis of manassantins A and B, potent inhibitors of HIF-1, is described. Central to the synthesis is a stereoselective addition of an organozinc reagent to a 2-benzenesulfonyl cyclic ether to achieve the 2,3-cis-3,4-trans-4,5-cis-tetrahydrofuran of the natural products. Preliminary structure—activity relationships suggested that the (R)-configuration at C-7 and C-7″′ is not critical for HIF-1 inhibition. In addition, the hydroxyl group at C-7 and C-7″′ can be replaced with carbony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…In this analysis, the endogenous proteins in a yeast cell lysate were analyzed for binding to manassantin A, a natural product that has been shown to have anti-cancer activity in cell-based assays but that has an unknown mode-of-action (1820). The LC-MS/MS data for this ligand-binding experiment were acquired on an orbitrap mass spectrometer with HCD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis, the endogenous proteins in a yeast cell lysate were analyzed for binding to manassantin A, a natural product that has been shown to have anti-cancer activity in cell-based assays but that has an unknown mode-of-action (1820). The LC-MS/MS data for this ligand-binding experiment were acquired on an orbitrap mass spectrometer with HCD.…”
Section: Resultsmentioning
confidence: 99%
“…A 20X inhibitor cocktail was prepared in which stock solutions of the inhibitors were mixed to give a final concentration of 0.2 mM pepstatin A, 0.4 mM leupeptin, 0.3 mM E-64, 1 mM bestatin, and 20 mM AEBSF. Manassantin A was prepared by total chemical synthesis and purified as described elsewhere (18). …”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that 1 exhibited a highly potent level of HIF-1 inhibitory activity in a luciferase-reporter based assay (IC 50 = 1–10 nM) 17. Based on the luciferase assay data, we used Western blots to further confirm the HIF-1 inhibitory activity of 1 .…”
mentioning
confidence: 96%
“…In broad connection with our interest in the stereoselective synthesis of substituted tetrahydrofurans,15,16 we recently completed the synthesis of 1 and 2 via a direct nucleophilic addition of an organozinc reagent to a 2-benzenesulfonyl cyclic ether to synthesize the 2,3- cis -3,4- trans -4,5- cis -tetrahydrofuran moiety of 1 and 2 17. In addition, we also showed that the ( R )-configuration at C-7 and C-7‴ is not critical for HIF-1 inhibition and that the hydroxyl group at C-7 and C-7‴ can be replaced with carbonyl group without significant loss of activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation